Programmable Granular Hydrogel Inks for 3D Bioprinting Applications - Ribeiro, Lucas S. (2023)
Granular inks comprising jammed hydrogel unit building blocks are emerging as multiprogramable precursors for 3D/4D printing nonbulk hydrogel constructs. In addition to their injectability, they also exhibit high porosity when compared to bulk hydrogels, allowing more efficient nutrient transport and cell migration through the scaffold structure. Herein, the key steps in the production of these inks, from the fabrication of the microgels, the jamming process, and how fabrication affects final material properties, such as porosity, resolution, and fidelity is reviewed. In addition, the main techniques used for the stabilization of scaffolds after the printing process and the assessment of cell viability, in the case of bioinks, are meticulously discussed. Finally, the most recent studies in the application of granular hydrogels for different biomedical applications are highlighted. All in all, it is envisioned that 3D-printed granular constructs will continue to evolve towards increasingly stimuli-responsive platforms that may respond in a spatiotemporally controlled manner that matches that of user-defined or biologically encoded processes.